2015
DOI: 10.1159/000430372
|View full text |Cite
|
Sign up to set email alerts
|

Isoliquiritigenin Inhibits Interferon-γ-Inducible Genes Expression in Hepatocytes through Down-Regulating Activation of JAK1/STAT1, IRF3/MyD88, ERK/MAPK, JNK/MAPK and PI3K/Akt Signaling Pathways

Abstract: Background & Aims: The high expression levels of interferon-γ (IFN-γ)-inducible genes correlate positively with liver diseases. The present study aimed to explore the effect of isoliquiritigenin (ISL) on the expression of genes induced by IFN-γ in vitro, and to elucidate the underlying molecular mechanisms. Methods: HepG2 and L02 cells were divided into control, ISL, IFN-γ, and IFN-γ plus ISL groups. The cytotoxicity of compounds to cells was evaluated by Cell Counting Kit 8 (CCK8) assay; the expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Activation of the PI3K/AKT pathway has been demonstrated to have neuroprotective effects against ischemia-induced neuron apoptosis (36). The Jak2/Stat3 cascade has been documented to be regulated by the PI3K/AKT pathway, mediating the functions in regulation of cell proliferation, anti-apoptosis and anti-senescence, cancer generation and migration, tissue development and memory formation (15)(16)(17). A study indicated that phosphorylation levels of AKT and Stat3 are increased after humanin acts on the GP130/IL6ST receptor complex (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the PI3K/AKT pathway has been demonstrated to have neuroprotective effects against ischemia-induced neuron apoptosis (36). The Jak2/Stat3 cascade has been documented to be regulated by the PI3K/AKT pathway, mediating the functions in regulation of cell proliferation, anti-apoptosis and anti-senescence, cancer generation and migration, tissue development and memory formation (15)(16)(17). A study indicated that phosphorylation levels of AKT and Stat3 are increased after humanin acts on the GP130/IL6ST receptor complex (11).…”
Section: Discussionmentioning
confidence: 99%
“…Jak2/Stat3 signaling is well documented to be regulated by the PI3K/AKT pathway (15)(16)(17). To understand the influence of the PI3 K/AKT pathway on Jak2/Stat3 signaling when HNG is used to counteract OGD/R of neurons, HNG was used in co-treatment with specific inhibitors of PI3K and AKT in OGD/R processes.…”
Section: Jak2/stat3 Signaling Mediates Neuroprotective Functions Of Hmentioning
confidence: 99%
“…In endometrial cancer cells, ISL was demonstrated to induce cell cycle arrest in the sub-G1 or G2/M phase through the p53/p21 pathway, and promote cell apoptosis and autophagy via activation of the extracellular signal-regulated kinase pathway (22). In addition, previous studies have demonstrated that the phosphatidylinositol 3-kinase (PI3K)/AKT serine/threonine kinase (AKT) signaling pathway is also involved in ISL-induced cell apoptosis and proliferation (23,24); however, the possible regulation of the PI3K/AKT signaling pathway and its downstream pathways by ISL in the context of lung cancer has received relatively little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in this study, we also acquired an understanding of the essential miRNA-mRNA interactive network on the basis of functional enrichment (Figure 4C). The corresponding target genes for the 11 hub miRNAs, including JAK1, MAPK1, STX3 and BCL10, are crucial regulators in cell cycle, gene expression, signal transduction and apoptosis[35-37]. Thus, identification of the target genes modulated by the dysregulated miRNAs will greatly promote our understanding of HBx-associated hepatocarcinogenesis and facilitate design of new targeted therapeutic agents.…”
Section: Discussionmentioning
confidence: 99%